Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.3390/genes14030637
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Association Study for Grain Protein, Thousand Kernel Weight, and Normalized Difference Vegetation Index in Bread Wheat (Triticum aestivum L.)

Abstract: Genomic regions governing grain protein content (GPC), 1000 kernel weight (TKW), and normalized difference vegetation index (NDVI) were studied in a set of 280 bread wheat genotypes. The genome-wide association (GWAS) panel was genotyped using a 35K Axiom array and phenotyped in three environments. A total of 26 marker-trait associations (MTAs) were detected on 18 chromosomes covering the A, B, and D subgenomes of bread wheat. The GPC showed the maximum MTAs (16), followed by NDVI (6), and TKW (4). A maximum o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 89 publications
1
4
0
Order By: Relevance
“…This study shows that a large proportion (89%) of the accessions have protein above 12%, and are suitable for preparing leavened breads [ 2 ]. The average grain protein values (13.4%) are similar to or higher than the reported information on protein contents in other bread wheat collections [ 19 , 27 , 28 , 31 , 34 ]. Additional research revealed that some accession sets had greater protein values (up to 20%), demonstrating the impact of genotype-by-environment interactions [ 22 , 23 , 33 ].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…This study shows that a large proportion (89%) of the accessions have protein above 12%, and are suitable for preparing leavened breads [ 2 ]. The average grain protein values (13.4%) are similar to or higher than the reported information on protein contents in other bread wheat collections [ 19 , 27 , 28 , 31 , 34 ]. Additional research revealed that some accession sets had greater protein values (up to 20%), demonstrating the impact of genotype-by-environment interactions [ 22 , 23 , 33 ].…”
Section: Discussionsupporting
confidence: 81%
“…Identifying marker-trait associations (MTAs) or quantitative trait nucleotides (QTNs) can make it easier for breeders to choose the best genotypes, reduce the breeding cycle, and achieve higher genetic gains. A number of recent GWAS studies reported genomic regions associated with GPC and yield components [ 14 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…The consistent SNP on chromosome 3B ( BS00062734_51 ) is located at the position of 545,069,014 bp on the IWGSC RefSeq v1.1 map and is, therefore, distant from the two significant SNPs identified on the same chromosome in the study by Alemu et al [ 17 ] within the intervals 822,819,158–822,820,535 bp, and 795,567,173–795,572,772 bp, as well as far from the five significant SNPs on 3B reported by Leonova et al [ 18 ], altogether located between 29,356,100 and 493,122,600 bp. It is also far from the reported GPC-SNPs on chromosome 3B ( wsnp_Ex_c20652_29734133 at 292,024,034 bp, and RAC875_c58159_989 at 564,248,743 bp [ 48 ], and AX-94746929 at 800,933,346 bp [ 50 ]). The positions of the two stable SNPs, identified in the present study on chromosome 3A ( Excalibur_c13709_2568 at 518,897,423 bp and wsnp_Ku_c7811_13387117 at 714,304,435 bp), are far from the significant GPC-QTL peaked by wsnp_Ku_c30545_40369365 at 363,458,708 bp [ 48 ], as well as far from the two significant SNPs on 3A detected by Leonova et al [ 18 ] in single crop seasons (located at 20,019,900 and 739,397,100 bp).…”
Section: Discussionmentioning
confidence: 93%
“…QTNs for GPC under limited water supply were located on chromosomes 1B, 2A, 2B, and 6B [ 49 ], of which the QTL 6B.7 was co-mapped with the previously cloned gene Gpc-B1 associated with high grain protein [ 20 ]. In total, 16 significant MTAs for GPC on chromosomes 1A, 1B, 1D, 2B, 3B, 4B, 5A, 5B, 5D, 6A, 6B and 7A have been identified in a set of 280 diverse bread wheat genotypes [ 50 ]. QTL hotspots harboring a number of significant MTAs for protein content have been recently reported on chromosomes 3B (13), 5A (2), 5B (6) and 7D (2) in a population of Mediterranean landraces [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation